Radość filozofa. Edyty Stein drogi radości - KOZŁOWSKI, Ryszard (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
In her philosophical and autobiographical writings, Edith Stein, philosopher and Carmelite nun, made many significant remarks concerning the phenomenon of joy and the experience of joy as such. Her pursuit for the source of joy comprised three stages: the period of her philosophical growth, the time of her focus on metaphysics, and the final period in which she was above all a mystic and in which she achieved a fulfillment of her quest. In each of these stages, however, the same joy was revealed to Edith Stein, albeit in different ways, its only source being the Incarnate Word of God. Thus she was able to clarify her vision of the essence of joy and to distinguish it from the lived experience of joy. To Edith Stein, genuine joy meant simultaneously eternal joy: it signified the joy that God himself grants to the human being. Edith Stein did experience the way of genuine joy. Although her life ended with a martyr’s death, it was joy that ultimately prevailed in it. Translated by Dorota Chabrajska